Development and validation of the European QUALity (EQUAL) score for mucormycosis management in haematology. (15th February 2019) - Koehler, Philipp; Mellinghoff, Sibylle C; Lagrou, Katrien; Alanio, Alexandre; Arenz, Dorothee; Hoenigl, Martin; Koehler, Felix C; Lass-Flörl, Cornelia; Meis, Jacques F; Richardson, Malcolm; Cornely, Oliver A
Abstract: Background: Mucormycosis is a life-threatening infection in immunocompromised patients and in haematological malignancy patients in particular. Objectives: Our aim was to develop and evaluate a scoring tool to measure adherence to current guidelines for mucormycosis. Methods: Current guidelines of scientific societies on mucormycosis management were reviewed. We assembled diagnostic, treatment and follow-up milestones and designed the EQUAL Mucormycosis Score. The EQUAL Mucormycosis Score was evaluated in the ECMM Excellence Centres. Results: An 18-item tool with one to three points per item resulted in a maximum achievable score depending on disease complexity and ranging from 25 to 32 points. Given variable patient disease course, the diagnostic score is higher in patients with positive fungal culture and biopsy, thus reflecting more decision points and higher management complexity. Eleven patients from two centres were included during the study period. A total of 200 EQUAL Mucormycosis Score points were achieved, which is 62.7% of the maximum EQUAL Mucormycosis Score of 319 points achievable in that cohort (median 18 points, range 7–27). The total score accomplished for diagnostic procedures was 112 of 165 points (67.9%), for first-line treatment 54 of 88 (61.4%) and for follow-up management 34 of 66 points (51.5%). Conclusions: The EQUAL Mucormycosis Score quantitates adherence to current guideline recommendations for mucormycosis management. With 62.7% of maximum achievable score points, a first result is obtained that may serve as a reference for future evaluations. It remains to be shown whether guideline adherence and mortality rates correlate.